Research progress on nursing of infusion extravasation of implantable central venous port system (植入式静脉输液港输液外渗的护理研究进展) - LI Hailu (李海璐); ZHANG Yun (张云); TIAN Shengnan (田胜男) (中西医结合护理)
A venous port system is designed to be implanted into the central venous system for a long time. As a common complication of chemotherapy through central venous port system, extravasation may lead to the interruption of treatments. This article analyzed the causes of infusion extravasation of implanted venous infusion port, describe the clinical manifestations of infusion extravasation, and put forward the countermeasures and preventive measures for infusion extravasation of implantable venous port. This study was expected to provide evidence and reference for the nursing of this complication in clinical practice. (植入式静脉输液港是一种可长期留置在体内的中心静脉输液装置, 静脉输液港使用过程中会出现药物外渗等并发症, 不利于患者后续治疗。本研究分析了植入式静脉输液港输液外渗的发生原因, 阐述了输液外渗的临床表现, 并提出了植入式静脉输液港输液外渗的应对策略及预防措施, 以期为临床护理实践提供参考。)